FAUNISTIC ANALYSIS OF NEMATODES OF WILD MEDICINAL PLANTS IN SURKHANDARYA REGION OF UZBEKISTAN - Muxlisa Turopova; Ma’suma Raxmatova; Abdujabbor Bekmurodov (The Bioscan, 2024)
The article provides data on the fauna, taxonomic composition and distribution of nematodes of some wild medicinal plants in the conditions of the Surkhandarya region of Uzbekistan. As a result of a study in the root system and rhizosphere of some wild medicinal plants (sea buckthorn, rose hips, barberry, hawthorn), 47 species of nematodes were identified, belonging to 31 genera, 19 families, 5 orders and 2 subclasses. The main faunal complex of nematodes of wild medicinal plants consists of the species Eudorylaimus labiatus, E. pratensis, Tylencholaimus minimus, Diphtherophora communis, Cephalobus persegnis, Chiloplacus sclerovaginatus, Eucephalobus oxyuroides, Panagrolaimus rigidus, Aphelenchus avenae, Aphelenchoides parietinus, A.limberi, cius capitatus, Helicotylenchus dihystera, H.erythrinae, Pratylenchus pratensis and Ditylenchus dipsaci.